TINJAUAN MENGENAI KOMODITI PERDAGANGAN BERJANGKA BITCOIN SEBAGAI ALAT TUKAR DALAM TRANSAKSI KEUANGAN ELEKTRONIK - Shafa Safira Diana (2022)
Modern digital-based financial technology is designed to facilitate access to financial transactions as part of trading activities that have been constrained by distance and time factors. One of the products of financial technology that is favored by many investors and traders in the world is cryptocurrencies (cryptocurrencies), one of them is Bitcoin. As a trading commodity popular in other countries, Bitcoin was initially popular among investor and traders in indonesia. the phenomenon of Bitcoin as a product of the development of modern financial technology which then has legality as a Futures Trading commodity in Indonesia. The research method that are writer use in this thesis is a normative juridical with descriptive analytical research). The normative juridical research method is a legal research by examining the literature or utilizing library materials and existing secondary data. The results obtained from this study refer to the existing regulations in Article 1 of the Regulation of the Minister of Trade Number 99 of 2018 concerning the General Policy for the Implementation of Crypto Asset Futures Trading, cryptocurrencies, including Bitcoin, are designated as Commodities. Then more than that, the Currency Law and several related regulations in Indonesia confirm that the legal tender in the territory of the Republic of Indonesia is Rupiah. The logical consequence of this is that banks or other financial institutions can refuse transactions using bitcoin as a medium of exchange, including electronic transactions.